HtrA3‐Mediated Endothelial Cell–Extracellular Matrix Crosstalk Regulates Tip Cell Specification. (24th May 2021) - Guo, Yaru; Ma, Siqin; Xu, Mingming; Wei, Yan; Zhang, Xuehui; Huang, Ying; He, Ying; Heng, Boon Chin; Chen, Lili; Deng, Xuliang
Abstract: Angiogenesis is critical in tissue engineering and regenerative medicine. Once initiated, outgrowing capillaries are spearheaded by specialized endothelial cells (ECs) termed tip cells. Specification of tip cells from ECs during angiogenesis is greatly influenced by the surrounding extracellular matrix (ECM). However, the crosstalk between ECs and the ECM in tip cell specification is poorly understood. Here, this study shows that the high‐temperature requirement A3 (HtrA3) protein is deeply involved in this process. Specifically, HtrA3 is upregulated in the frontal area of tissue repair and cancer progression through VEGFR2 activation by VEGF in ECs. Secreted HtrA3 degrades the surrounding Collagen IV, which provides space for tip cell morphogenesis and exposes integrin β1‐related ligands. Integrin β1‐ligand binding activates PI3K/AKT/mTOR signaling, which subsequently suppresses the Notch signaling pathway, eventually promoting tip cell specification. Moreover, local administration of exogeneous recombinant HtrA3 in rat cranial bone defects significantly increases blood vessel formation. Conversely, injection of HtrA3 siRNA decreases developmental retinal angiogenesis. These data show that HtrA3 mediated crosstalk between ECs and the ECM enhances tip cell specification of ECs. Hence, HtrA3 can act as a therapeutic agent for improving angiogenesis in situations in need, as well as serve as a therapeutic target for pathological angiogenesis. Abstract : HtrA3‐medicated ECM‐ECs crosstalk is deeply involved in tip cell specification. Specifically, HtrA3 is upregulated through VEGFR2 activation by VEGF in ECs. Secreted HtrA3 degrades the surrounding Collagen IV, which provides space for tip cell morphogenesis and exposes integrin β1‐related ligands. Integrin β1‐ligand binding activates PI3K/AKT/mTOR signaling, which subsequently suppresses the Notch signaling pathway, eventually promoting tip cell specification.